Crisis of Agency in Central and Eastern Europe: From the Consolidation of Media Freedom to the Institutionalisation of Free Choice - Balčytienė, Auksė (Javnost-The Public, 2021)
This paper explores current result of gradual structural changes affecting news media environment in Poland. Its main argument is that these developments have led to a growing structural polarisation. Such polarisation penetrates news media coverage, journalistic community setup and self-regulatory frameworks, users’ perspectives and various news media spaces, including mainstream media and digital natives. The gaps grow between societal camps with liberal and conservative orientations, young and old, urban and non-urban communities, well and poorly educated.